1977
DOI: 10.1055/s-0028-1094547
|View full text |Cite
|
Sign up to set email alerts
|

Indication of an Antipsychotic Action of the Opiate Antagonist Naloxone

Abstract: In 20 psychotic patients with frequent hallucinations and/or actual delusional experience a possible antipsychotic action of the opiate antagonist naloxone (N-allyl-noroxymorphone) was investigated, using a double-blind placebo-controlled cross-over design. 18 of these patients were not treated with neuroleptic drugs; 13 suffered from an acute episode of schizophrenia. Psychopathological changes were assessed by the use of the IMPS-scale and of a symptom-specific rating scale (VBS). Intravenous injection of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…W niektórych przypadkach nalokson powodował całkowite ustąpienie objawów psychotycznych, szczególnie halucynacji w schizofrenii [100].…”
Section: Egzorfinyunclassified
See 1 more Smart Citation
“…W niektórych przypadkach nalokson powodował całkowite ustąpienie objawów psychotycznych, szczególnie halucynacji w schizofrenii [100].…”
Section: Egzorfinyunclassified
“…In some cases, naloxone caused complete disappearance of psychotic symptoms, particularly hallucinations in schizophrenia [100].…”
Section: Exorphinsmentioning
confidence: 99%
“…The endogenous opioid system has also been implicated in the pathophysiology of psychotic behavior (Gunne et al, 1977) and manic-depressive illness (Watson et al, 1949). The opiate receptor antagonist naloxone was reported to ameliorate psychotic symptoms (e.g., auditory hallucinations) in schizophrenic subjects (Gunne et al, 1977;Emrich et al, 1977) as well as to ameliorate obsessive-compulsive behavior (Insel & Pickar, 1983). The high density of opioids and their receptors in the limbic system (Cuello, 1983), and the presence of opioid containing neurons-on dopamine nerve terminals makes it likely that the opioids modulate behavioral and cognitive functions in humans.…”
Section: The Opioid System In Tsmentioning
confidence: 99%
“…4 o f the patients showed transient reduction or even disappear ance o f the psychotic symptoms, and particu larly o f auditory hallucinations. In four double blind, placebo-controlled studies a single intra venous doses o f naloxone was given to 20, 11,8 and 7 patients with schizophrenic psychosis, respectively (Emrich et al, 1977;Watson et al, 1978;A kil et al, 1978;Lehman et al, 1979). Emrich et al (1977) gave 4.0 mg naloxone, while the other authors used a dose o f 10 mg.…”
mentioning
confidence: 99%
“…In four double blind, placebo-controlled studies a single intra venous doses o f naloxone was given to 20, 11,8 and 7 patients with schizophrenic psychosis, respectively (Emrich et al, 1977;Watson et al, 1978;A kil et al, 1978;Lehman et al, 1979). Emrich et al (1977) gave 4.0 mg naloxone, while the other authors used a dose o f 10 mg. In these four studies, a total o f 32 patients showed reduction o f psychotic symptoms (again in particular o f auditory hallucinations) 2 7 h after the injection.…”
mentioning
confidence: 99%